2015
DOI: 10.7860/jcdr/2015/12888.6402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Choroidal Thickness and Volume during the Third Trimester of Pregnancy using Enhanced Depth Imaging Optical Coherence Tomography: A Pilot Study

Abstract: Our study suggests that in the third trimester of pregnancy the choroid may be subjected to physiological changes in structure. Whether these changes are a result of hormonal and/or haemodynamic adaptations of pregnancy remains to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…There are more than a dozen studies on choroidal thickness changes in pregnancy using enhanced depth imaging OCT, which have provided inconsistent results. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Some studies have found thickening of the choroid in specific subfields during the second and third trimester of pregnancy, whereas other studies have observed no difference in choroidal thickness during pregnancy. The discrepancy in these studies could be due to variation in inclusion criteria, confounding factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than a dozen studies on choroidal thickness changes in pregnancy using enhanced depth imaging OCT, which have provided inconsistent results. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Some studies have found thickening of the choroid in specific subfields during the second and third trimester of pregnancy, whereas other studies have observed no difference in choroidal thickness during pregnancy. The discrepancy in these studies could be due to variation in inclusion criteria, confounding factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing choroidal thickness in nonpregnant and pregnant women provide contradictory results. According to some studies, a statistically significant thickening of the choroid occurs during pregnancy [ 9 , 19 , 21 26 , 29 ], whereas other studies do not show such a relationship [ 20 , 26 ]. Also, the results concerning the relationship between choroidal thickness and gestational age differ [ 9 , 20 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the EDI-OCT examination performed three months after childbirth, a decrease was observed in the choroidal thickness, compared to the period of pregnancy [ 22 ]. Ataş et al, and Rothwell et al, in their studies, examined women in the third trimester of pregnancy, and also found that in these women the choroidal thickness was significantly higher statistically, compared to women who were not pregnant [ 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different control group of non-pregnant women was also analyzed and showed significantly thinner choroid measurements in comparison with pregnant women. Rothwell et al [ 31 ] used a different technique to analyze choroid structure by constructing volume macular maps for the 9 subfields defined by the Early Treatment Diabetic Retinopathy Study. The measurements of thickness and volume in the central subfield were significantly greater in third trimester pregnant patients than in non-pregnant patients.…”
Section: Discussionmentioning
confidence: 99%